Study of fuel cell and gas turbine hybrid power systems - Basurto, M. T. (Cranfield University, 2002)
Environmental awareness and the interest in distributed generation caused by electricity market de-regulation are factors that promote research on renewable energies. Fuel cells transform the chemical energy stored in fuel into electricity by means of electrochemical reactions. Among the different fuel cell types, high temperature fuel cells (HTFCS) have many advantages: high efficiency, low emissions, fuel flexibility, modularity and high quality waste heat. The main disadvantage is their high cost - however, this will be reduced when HTFCS are commercialised. The synergy between HTFCS and gas turbines (GTS) makes HTPC/GTS very efficient power systems for the generation of electricity, from kilowatts to just a few megawatts. The present work focuses on HTFC/GT power systems, analysing their performance, studying some particular applications, and making an economic assessment. The final objective of this Thesis is to define a procedure to assist in the preliminary design of HTFC/GT systems. The authors main contribution is the definition of the Green-Cell Code capable of simulating HTFC/GT systems, the study of their interest for several applications, and the generation of a decision-making method for the preliminary design of HTFC/GT systems. The design and off-design simulation of HTFC/GT cycles have been carried out with the integration of a code developed by the author to simulate HTFC performance, and a commercial code to simulate GT performance. This work is even more valuable given the lack of commercial tools to analyse the system. All of the technical and economic work is collected in a set of charts that assist the procedure of HTFC/GT cycle selection. These charts show that HTFC/GT systems currently achieve thermal efficiencies of about 60%, and will be capable of achieving up to 73% in the future. This is of great interest for power generation applications. The use of a recuperate is required to optimise the performance of the gas turbine and the fuel cell; it is also interesting to use it to generate the maximum amount of power from the HTFC, in order to reduce emissions and increase overall efficiency. Results show that Pressurised MCFC/GT Cycles achieve better performance and economic results that Atmospheric MCFC/GT Cycles. For Pressurised MCFC/GT Cycles, the optimum stack operating pressure is between 5 and 10 bars. The installation of a combustor in Pressurised MCFC/GT cycles leads to higher specific power, higher unit costs of electricity, higher CHP efficiency, and lower thermal efficiency. The use of HTFC/GT cycles to generate heat and power must be seen as a way to improve HTFC/GT efficiency by using the waste heat of exhaust gases, rather than as an optimum application. Results also show that SOFC/GT systems achieve slightly higher results than MCFC/GT systems. Thus, the choice between MCFCs and SOFCs will be based on durability and cost issues rather than on performance issues.